Activity of combinations of bactericidal and bacteriostatic compounds in Mycobacterium abscessus-infected mice: an overview - Lanni, Alessio; Iona, Elisabetta; Fattorini, Lanfranco; Giannoni, Federico; Iacobino, Angelo (Frontiers in Microbiology, 2025)
Treatment of Mycobacterium abscessus (MAB) infections is complicated by the lack of bactericidal antibiotics, the ability of MAB to persist in the hypoxic environment of granulomas and the intrinsic antibiotic resistance, which results in patient treatment with drug combinations for several months. Therefore, the search for new drugs/drug combinations is an urgent need. This review provides a comprehensive update on the activity in the lungs of MAB-infected mice of new and old bactericidal and bacteriostatic compounds, alone and in combination, which showed killing greater than or equal to clinically used antibiotics and combination components. The acute model (4–14 days of treatment) was preferred in most single-drug efficacy testing procedures while the chronic model (28–42 days) was primarily used for combinations. Overall, 15 of 17 new compounds and 13 of 14 combinations decreased MAB colony forming units (CFUs) more than comparator drugs or combination components. The most potent combinations were those formed by bactericidal agents (≥1−log10 CFU reduction compared to the initial bacterial burden), consisting of two β-lactams and a β-lactam plus a β-lactamase inhibitor. Among the other combinations, activity of the bactericidal compounds was usually slightly increased by the bacteriostatic agents that, however, preserved the bactericidal core of combinations and suppressed emergence of drug resistance. Overall, these data suggest that there is an urgent need for systematic in vivo investigations on anti-MAB activity of combinations containing bactericidal drugs that are part of current treatment guidelines or of new, preferably oral compounds, to ultimately eradicate non-replicating persisters at the sites of disease.